The Arabic Voiced Sounds in the Orientalists - حسين علي الفضليّ بشرى (Al-Adab Journal, 2018)
The Arabic voiced sounds has obtained the interest of Orientalists, who agreed that the number of voiced sounds in Arabic are six: three are short (fatha, kasra and dhama), and three are long (alef, wow and yaa). The Orientalist Bragister had a different view. He sees that the voiced sounds are two not three and that fatha is a full accent, while kasra and dhama are imcmplete ones. The Orientalists were concerned with the study of long and short voiced sounds in the writings of the Arabic language scholars and scholars of recitation. The lengthening voiced sounds in Arabic had a share in their research which are: extension, amplification, prolonging and deflation.